Impact of prenatal perineal massage and pelvic floor relaxing exercises on obstetric outcome: A prospective randomized controlled trial - Loonaich, Nikita; Jain, Shaveta; Dahiya, Pushpa (Asian Journal of Medical Sciences, 2025)
Background: Normal vaginal delivery is associated with a significant risk of perineal trauma and associated complications. This can be avoided by engaging in prenatal pelvic floor exercises, yoga, and perineal massage. Exercise and perineal massage significantly improve maternal and neonatal outcomes and reduce postpartum complications. Aims and Objectives: To study the impact of prenatal perineal massage and pelvic floor relaxing exercises on obstetric outcome, incidence of episiotomy, mode of delivery, duration of labor, and postpartum complications in women of both groups. Materials and Methods: This prospective randomized controlled trial study was conducted in a tertiary care hospital in Northern India. 200 primigravida antenatal women with uncomplicated singleton pregnancy at the period of gestation ≥32 weeks who attended the antenatal outpatient department, Post Graduate Institute Memory Scale were included in the study and were divided into two groups: Group A (performing perineal massage and pelvic floor exercises) and Group B (receiving routine antenatal care). Patients were followed till 6 days postpartum and data were collected regarding fetomaternal outcomes. Results: From Group A, 80% of participants had spontaneous onset of labor as compared to 64% in Group B (P=0.012). In the present study, the mean duration of the first stage of labor was 232.84±29.88 min and 245.39±26.13 min, respectively, which was significantly reduced in Group A (P<0.004). Similarly, the duration of the second stage of labor was significantly reduced in Group A, 44.2±10.73 min in Group A, and 58.02±20.81 min in Group B (P<0.001). A significant reduction was seen in the need for episiotomy and postpartum complications in Group A, (P<0.0001) and (P=0.003), respectively. Conclusion: The findings of this study suggest that engaging in perineal exercises and massage has contributed to shortening the duration of labor with a significant reduction in rates of episiotomy and 2nd perineal tear, hence leading to less number postpartum complications such as infection and episiotomy gaping.